DEPOSITION COATING EFFICIENCY OF 67Ni18Cr5Si4B COATING POWDER ON C45 STEEL BASE MATERIAL USING DATA ENVELOPMENT ANALYSIS - Emorinken, Samuel Olayinka; Ogunmola, Bayo Yemisi; Alozie, Nehemiah Sabinus; Oluwo, Adeyinka; Rajan, John; Jose, Swaminathan; Oke, Sunday Ayoola (International Journal of Mechanical Engineering Technologies and Applications, 2025)
The astronomical increase in the cost of inputs for the coating process without a corresponding increase in market share and prices of goods is a threat to surface coating manufacturers. Despite this threat, very few discussions focus on the efficiency of the coating process. The purpose of this paper is to analyse the efficiency of the coating process while using the 67Ni18Cr5Si4B coating powder on C45 steel substrate material. The data envelopment analysis was used to obtain the relative efficiency of parameters, namely, spray velocity, powder feed rate, spray distance, porosity, adhesion strength, and microhardness. This in turn contributed to analyzing the efficiencies of the levels of the inputs to provide efficiency information on the output from the averages. Data envelopment analysis regards inputs and outputs as decision-making units (DMUs) and is operated by minimizing inputs or maximizing the outputs. Using data envelopment analysis to obtain the relative efficiency of coating powder becomes an enlightening practice. With this, the levels of each system were termed to be efficient, if the efficiency factor (hk) is equal to one. In a real sense, the levels could be obtained by calculating the average values regarding a parameter. The result of the study was enhanced with the aid of the linprog facility in Matlab. The efficiency was obtained for each level as 0.92,1, and 1 respectively. Hence, levels 2 and 3 are efficient but level 1 is inefficient according to the data envelopment analysis. On average, the overall efficiency is 0.95 which is termed inefficient.